Doxycycline Induces Mitophagy and Suppresses Production of Interferon-β in IPEC-J2 Cells - Xing, Yang; Liqi, Zhu; Jian, Lin; Qinghua, Yu; Qian, Yang (Frontiers in Cellular and Infection Microbiology, 2017)
Abstract: Previous reports have demonstrated that the second-generation tetracycline derivative doxycycline (DOX) interrupts mitochondrial proteostasis and physiology, inhibits proliferation of many cell types, and induces apoptosis. However, the effects of DOX, which is widely used in porcine husbandry by feed, on the porcine intestinal epithelium are unclear. In this study, we demonstrated that DOX damaged mitochondrial morphology and induced the co-localization of mitochondria with autophagosomes, suggesting that DOX induces mitophagy in IPEC-J2 cells. We also found evidence that DOX increased intracellular levels of reactive oxygen species (ROS) or mitochondrial-specific ROS in a dose dependent manner. Moreover, 50μg/ml DOX significantly decreased production of interferon-β and facilitated replication of transmissible gastroenteritis coronavirus in IPEC-J2 cells. These results demonstrated that DOX induced mitophagy and ROS production, which damaged the intestinal epithelium. As DOX is used extensively in pig husbandry, uncontrolled application poses a significant threat of viral infection, so stricter policies on its usage should be required.